Peningkatan Stabilitas Transien pada Turbin Angin Berbasis DFIG Menggunakan SFCL tipe Bridge - Doane Puri Mustika; Sasongko Pramono Hadi; Mokhammad Isnaeni B; Mohd. Brado Frasetyo; Tumiran (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
Today’s electrical energy is mainly produced by burning fossil fuels, which actually has negative effects on earth, namely global warming. In the electricity sector, measures that can be taken to reduce emissions include replacing conventional generators with renewable ones. Wind energy is one type of new renewable energies (NREs) with the potential to reduce emissions. Wind turbines widely used today are variable speed wind turbines, such as the doubly-fed induction generator (DFIG). DFIG has numerous advantages, like having more flexibility and being able to control both active and reactive powers. However, it often encounters instability problems in its system when experiencing transients. Therefore, a solution that can improve transient stability in DFIG is needed. The bridge-type superconducting fault current limiter (SFCL) was used in this research as a solution to improve the transient stability in DFIG, which consisted of two diodes and two inductors. This bridge-type SFCL operates by limiting the current in the event of faults, preventing the system from voltage drops or trips. The simulation results were analyzed under two circumstances. In the first circumstance, the 9 MW DFIG wind turbine system which was given faults using SFCL produced a voltage value of 219 V, with a more stable frequency value of 50 Hz, and an active power value of 9 MW. Meanwhile, when a system that did not use SFCL was given faults, the voltage dropped from the normal state of 219 V to 100 V. The frequency value was less stable, fluctuating between 49.75 Hz and 50.25 Hz, while the active power dropped from 9 MW to 6 MW. This result proves that the bridge-type SFCL method effectively increases the transient stability in DFIG.